Biodiversity threats and socio-ecological dynamics in Chebera Churchura National Park: A one health approach - Guadu, T.; Abera, B.; Tesfay, K.; Berhane, A.; Tafese, A.; Solomon, T.; Debebe, B.; Getachew, M.; Shibabaw, A.; Araba, A.; Abdurahman, M.; Yadeta, W.; et al. (Elsevier, 2025)
Chebera Churchura National Park (CCNP), a protected area in Ethiopia renowned for its diverse and thriving ecosystems, including nearly one-third of the nation's African elephant population and the largest concentration of African buffalo, grapples with pressing conservation challenges. We conducted a study in 2024 in the Konta and Dwauro Zones to assess the park's conservation status and ecosystem services using a One Health (OH) approach. The study utilized a mixed-method approach using the Rapid Assessment and Prioritization of Protected Area Management (RAPPAM) tool, field observations, document reviews, and key informant interviews across human and animal health, agriculture, local administration, and environmental sectors in five purposefully chosen kebeles bordering the park. Findings showed that the conservation status and ecosystem services of CCNP were inadequate, with key challenges including expansion to the park, deforestation, and illegal logging, leading to habitat loss, increased poaching of high-value species, and frequent regular human-wildlife conflicts. The problem is exacerbated by inadequate financial, human, and infrastructural resources for effective park management. Outbreaks of vector-borne diseases like malaria and trypanosomiasis in nearby communities and animals, respectively, and neglected tropical diseases such as schistosomiasis and onchocerciasis were found to prevail. Lack of collaboration among stakeholders and limited support for park management from the local government and the public at large were critical gaps. In conclusion, the study underscored the need for multisectoral collaborative engagements, strong partnerships, and improved governance and resources to enhance conservation strategies, improve community health, and ensure the sustainable management of CCNP. Cross-sectoral alliance is essential for good governance, optimizing resource allocation, and advancing effective conservation practices to address the multifaceted challenges confronting the park despite its biodiversity hotspot of global significance.